Module Based on Pedagogical Content Knowledge to Increase the Engagement and Skills of the Future Teachers in Designing a Lesson Plan - Ika Maryani; Sri Tutur Martaningsih; Caraka Putra Bhakti (Intelektual Pustaka Media Utama, 2017)
Lesson plans is the most important component in preparing a quality learning. Teachers’ low understanding on pedagogical content knowledge affects their skills in designing learning. It needs serious effort to equip future teachers with pedagogical content knowledge to produce professional teachers. The aim of this study is to increase the engagement and skills of future teachers in designing lesson plans using module based on pedagogical content knowledge. College-students engagement indicators are adopted from Students Engagement Instrument (SEI)-Appleton, Christenson, Kim, and Reschly, consisting of affective and cognitive engagement. The skill in question are the ability to writing the subject’s identity, writing competencies, formulating indicators, compiling teaching materials, designing media, choosing learning method, compiling learning scenarios, as well as designing assessment. This research is a classroom action research that is designed in two cycles of learning with the number of respondents is 73 college-students. Each learning cycle is consisting of planning, implementation, observation, and reflection. The data collection techniques was self-report, observation, portfolios, interviews, field notes, and study documentation. Descriptive statistics were used to analyse the quantitative data, whereas qualitative data were analysed by qualitative analysis of Miles and Hubberman model. The results showed that the PCK-based module is able to increase college-students engagement and ability in designing a lesson plan.